Acceptance of Mass Drug Administration for Prophylaxis against Lymphatic Filariasis in a Tribal Endemic Area: A Descriptive Cross-sectional Study - Asmit Agarwal; Vikas Maharshi (Indian Journal of Public Health)
Background: India is at a critical stage to eliminate filariasis. Uncovering the factors governing may help taking appropriate measures to achieve the goal. Objectives: This study evaluated the acceptance of “mass drug administration” (MDA) for prophylaxis against filariasis and the factors facilitating and interfering with it. Materials and Methods: A cross-sectional study was conducted in a tribal endemic area of India from May 2022 to October 2022. A validated 29-item self-administered questionnaire was used to collect the data. Items were grouped under “knowledge,” “social processes,” “think and feel,” “practical factors,” and “motivation/hesitancy” domains. Results: Of 101 participants, majority were aware of the disease (92.1%), its vector (74.3%), at least one disability caused (87.2%), and governmental scheme of MDA (69.3%). Two-thirds never received and 85.1% did not receive MDA within 1 year. 68.3% refused of distribution of MDA to their doorstep. Majority were concerned for getting MDA for self and their family/friends; however, 49.5% showed inability to take independent decision. More than 30% disagreed to get MDA had it been available. The region with the highest concerns for adverse drug effects showed minimum MDA consumption than others (P < 0.05). MDA acceptance/consumption was significantly associated with knowledge about disability caused, distribution of drugs by a health-care representative to doorstep, behavior of the representative, and concerns about potential adverse drug effects. Conclusion: MDA coverage was inadequate in the study population. Level of knowledge, practical difficulties in getting drugs, inapt thinking/concerns, motivation, awareness about disabilities caused, door-to-door drug distribution, and behavior of health-care representative(s), were identified as factors significantly affecting acceptance of MDA.